O viver na família contemporânea: certezas, inquietações e possibilidades - Barbin, Lucelene Ferreira (2015)
Before long, the world s format was radically transformed by the arrival of globalization and all of what, unprecedentedly, was put at man s disposal technology, goods, service, among others. This is precisely a study about the family in this Postmodern context, where truths and certainties were relativized giving rise to doubts and uncertainties, according to the theorists that describe it. Therefore, we conducted a qualitative research from the perspective of the new paradigmatic systemic conception, whose point of view is the construction of the reality as a theoretical framework, through a semi-structured interview with couples who formed families that effectively live contemporary realities, so that they could narrate with their own voice how it is do be a family and to live as a family in this context. The analysis of the narratives led to the following thematic categories: "The Representation of Family s Sense and Meaning"; "Values"; "Rituals"; "Contemporary Aspects that Complicate the Relations in the Current Family". It was found that the resulting transformation of paradigmatic changes that gave rise to what we call Postmodernity also affected the traditional family, which remains under multiple configurations, settled mainly in the sense of family based on affection involving its members. Furthermore, it was also established that one of the main points of maintenance for the existence of the family is the practice of family rituals, moments in which comes to members of the family set a sense of belonging and unity in relation to the family as a whole. If affection is the basis of family formation, rituals are the glue that holds it together. An important point noted in relation to the rituals is the intentionality that makes possible its realization